Pelatihan Penguatan Branding, Storytelling, dan Promosi Berbasis Media Sosial Bagi Komunitas Sahabat GTI - Mazia, Lia; Zuniarti, Ida; Astuti, Widi; Rusmawati, Cikal Pustiprayata; Zhafira, Ryanne (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
Workshop on strengthening branding, storytelling, and social media-based promotion has been carried out to help female culinary entrepreneurs in the Sahabat Genggam Teman Indonesia (GTI) Community in Bekasi City enhance their digital skills. The training took place on Saturday, September 20, 2025, at the computer laboratory of Universitas Nusa Mandiri Jatiwaringin, Central Jakarta, as part of the 2025 DPPM Grant Program from the Ministry of Higher Education, Science, and Technology (Kemdiktisaintek). This community service activity aimed to improve the digital skills of female culinary entrepreneurs in the Sahabat GTI Community in Bekasi City through training in branding, storytelling, and social media-based promotion. The challenges faced were low understanding of consistent branding, effective storytelling techniques, and appropriate digital promotion. The methods used in this activity included practical training, simulations, and interactive discussions focused on improving participants' skills in creating logo designs, crafting product narratives, and utilizing social media as an effective promotional tool. The results of the training showed significant improvement, with an average increase of 85%, especially in branding and the use of social media for promotion. This training successfully provided a positive impact in enhancing participants' digital competence, which in turn can improve the competitiveness of their culinary businesses in the digital market. Empowering female MSME entrepreneurs through this training opens opportunities for the development of more professional and sustainable local culinary businesses in the global market.